2003
DOI: 10.4269/ajtmh.2003.69.213
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Endoscopic Findings Associated With Blastocystis Hominis in Healthy Adults

Abstract: Ninety-nine individuals with stools positive for Blastocystis hominis but negative for other parasites were identified from medical records of healthy adults who had received a physical examination at Taipei Veterans General Hospital from November 2000 to October 2002. The medical records of these 99 positive cases and 193 randomly selected controls, matched for age, sex, and date of examination, were retrospectively reviewed. The pathogenicity of B. hominis could not be demonstrated due to a lack of associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 27 publications
(45 reference statements)
4
34
2
Order By: Relevance
“…This is in contrast to reports that suggested otherwise (43,131,180,274). Certain populations may be susceptible to Blastocystis-associated disorders, and risk factors (176,196) and children with nephrotic syndrome receiving corticosteroids (173).…”
Section: Epidemiology and Prevalencecontrasting
confidence: 56%
See 2 more Smart Citations
“…This is in contrast to reports that suggested otherwise (43,131,180,274). Certain populations may be susceptible to Blastocystis-associated disorders, and risk factors (176,196) and children with nephrotic syndrome receiving corticosteroids (173).…”
Section: Epidemiology and Prevalencecontrasting
confidence: 56%
“…There are no reports of Blastocystis-associated dysentery, and it appears that the parasite is generally noninvasive, as indicated by endoscopy (43,76,329,330) and histology of experimentally infected animals (5,152,187). An interesting case study described Blastocystis trophozoites present in the liver abscess aspirate of a 63-year-old man with a 5-day history of fever and blood-tinged watery diarrhea (102).…”
Section: Infection and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…is not associated with pathogenicity. [12][13] There are different subtypes of Blastocystis spp. based on genotyping data.…”
mentioning
confidence: 99%
“…Most large studies of symptomatic Blastocystis patients describe a non-inflammatory watery diarrhea with no mucosal ulceration or invasion (Zuckerman et al 1994;Jelinek et al 1997). This study is the first to examine the small bowel in Blastocystis infection, as previous studies have not reported inspecting the terminal ileum at lower endoscopy (Kain et al 1987;Zuckerman et al 1994;Chen et al 2003). Prominent lymphoid tissue in the terminal ileum was the only mucosal abnormality seen in a minority of patients.…”
Section: Clinical Follow Up At 6 Weeksmentioning
confidence: 86%